Applicability of computational fluid dynamics to simulate ozonation processes (2011)
AbstractThis paper presents an integrated mathematical model based on the principle of computational fluid dynamics along with the kinetics of ozone decay and microbial inactivation to predict the performance of ozone disinfection in fine bubble column contactors. The model can be represented using a mixture two-phase flow model to simulate the hydrodynamics of the water flow and using two transport equations to track the concentration profiles of ozone and microorganisms along the height of the column, respectively. The applicability of this model was then demonstrated by comparing the simulated ozone concentrations with experimental measurements obtained from a pilot scale fine bubble column. Excellent agreement was obtained in terms of the dissolved ozone and the degree of microorganism inactivation without any pre-assumption about flow backmixing or dispersion level. It was also confirmed that in some cases, the presence of dead space or short-circulation could greatly affect the effective contact time for the dinfection to occur. This suggests that the great opportunity may exist to improve the efficiency of ozonation contactors in practice. The future work of this investigation is to confirm the numerical prediction of inactivation contour diagrams.